Effect of occupational noise on the course and outcome of pregnancy. - Hartikainen, A. L.; Sorri, M.; Anttonen, H.; Tuimala, R.; Laara, E. (Scandinavian Journal of Work, Environment & Health, 1994)
OBJECTIVES--The goal of this investigation was to examine the effects of occupational noise during pregnancy prospectively. METHODS--The exposed group [continuous A-weighted sound level (LAeq(8 h)) > or = 78 dB] consisted of 111 pregnant women, and the reference group comprised 181 pregnant women with approximately similar work conditions but without noise exposure. The noise-exposed women had more frequently other inconveniences in their work, however, like shift work, impulse noise exposure, vibration, and a high or low temperature. RESULTS--With the limit of 78 dB (LAeq (8 h)), the course and outcome of pregnancy did not differ between the groups. When the noise exposure was 90 dB (LAeq (8 h)) or more, a decline in birthweight, either absolute [mean 3304 (SD 585) g for the exposed versus mean (SD 548) g for the unexposed, 95% CI of mean difference -471--+15 g] or related to the gestational age (below the 10th percentile [5 of 25 (20%) versus 13 of 180 (7%)]), was seen. These findings were more pronounced if the woman was simultaneously exposed to a standing work position or shift work. CONCLUSIONS--Working in high noise exposure can be considered a form of risk during pregnancy.